Quantum wires : an overview - Ghatak, Kamakhya Prasad (Nanotechnology science and technology series., 2020)
"The Quantum Wires (QWs) occupy a central position in the whole field of nano-science and technology. In this edited book, in Chapter 1, the Fowler-Nordheim Field Emission from QWs has been studied and, in Chapter 2, the Effective Mass in Heavily Doped (HD) QWs has been investigated. The importance of Dispersion Relations is already well-known since the inception of Solid State Science, which has been studied in Chapter 3 in QWs of technologically important Non- Parabolic compounds. The Diffusivity Mobility Ratio and the Magneto Thermoelectric Power in QWs have been investigated in Chapters 4 and 5, respectively. In Chapters 6 and 7, the density-of-states function in HD superlattices in the presence of electric field has been explored as well as the Quantum Capacitance in Quantum Wire Field Effect Transistors. The importance of Einstein's Photoemission is already well-known and has been studied from Heavily Doped QWs in Chapter 8. In Chapter 9, the Magnetic susceptibility in the Magnetic Susceptibilities in QWs has been explored and, lastly, Chapter 10 discusses the Heisenberg's Uncertainty Principle (HUP) and the Carrier Contribution to the Elastic Constants in HD Opto electronic QWs. This edited book is written for graduate and post graduate students, researchers, engineers and professionals in the fields of mechanical engineering, electrical and electronic engineering, semiconductors and related areas, nano-electronics, condensed matter physics, solid state sciences, materials science, nano-science and technology and nano-structured materials in general"--